The foot-in-the-door compliance procedure a multiple-process analysis and review - Burger, Jerry M. (1999)
Research on the social compliance procedure known as the foot-in-the-door (FITD) technique is reviewed. Several psychological processes that may be set in motion with a FITD manipulation are identified:Self-perception, psychological reactance, conformity, consistency, attributions, and commitment. A review of relevant investigations and several meta-analyses support the notion that each of these processes can influence compliance behavior in the FITD situation. I argue that the combined effects of these processes can count for successful FITD demonstrations as well as studies in which the technique was ineffective or led to a decrease in compliance. The experimental conditions most likely to produce an FTD effect are identified.